The KISS1 metastasis suppressor appears to reverse the Warburg effect by shifting from glycolysis to mitochondrial beta-oxidation - Manley, Sharon J. (J Mol Med (Berl), 2017)
The shift by cancer cells toward aerobic glycolysis (Warburg effect) confers selective advantages by utilizing nutrients (e.g. lipids, amino acids and nucleotides) to build biomass. Lipogenesis is generally enhanced and its inhibition diminishes proliferation and survival. Re-expression of the metastasis suppressor KISS1 in human melanoma cells results in greater mitochondrial biogenesis, inhibition of glycolysis, utilization of beta-oxidation to provide energy, elevated oxidation of exogenous fatty acids and increased expression of early-phase lipogenesis genes at both mRNA and protein levels. Correspondingly, the energy sensor AMPKβ is phosphorylated, resulting in inhibitory phosphorylation of acetyl-CoA carboxylase (ACC), which is linked to enhanced beta-oxidation. Furthermore, PGC1α is required for KISS1-mediated phosphorylation of ACC and metastasis suppression. Collectively, these data further support the linkages between macromolecular metabolism and metastasis.